Development of Scrapbook Media Using the Canva Application for Class V Science Learning in Primary School at Primary School Negeri 139 Palembang - Rana Tin Duri; Sukardi Sukardi; Mega Kusuma Putri (Edumaspul: Jurnal Pendidikan, 2024)
Along with the development of increasingly rapid technological developments in the era of globalization, where humans need technology for their daily needs. Scrapbook is the art of sticking to a medium (usually paper), starting from sticking photos, leftovers, and others according to creativity, besides that scrapbooks can also make important notes related to pictures, words, or plans for learning materials This study uses a type of research and development called R&D (Research and Development). In this case, the researcher developed a scrapbook learning media assisted by digital canva in learning science on ecosystem material, the relationship between living things in the ecosystem. Interview collection technique Questionnaire Documentation Validity data analysis technique and Practicality data analysis technique. Based on the results of the practicality using one-to-one with an average value of 4.4 with a very practical category, the small group stage with an average value of 4.5 with a very practical category. Based on the results of the student response questionnaire obtained an average of 92% with very practical criteria at the one-to-one stage, and 95% at the small group stage. Based on the research results obtained at the one-to-one stage, the average value was 98.6%, which is included in the very practical category. The small group stage received an average value of 97.2%, which is categorized as very practical.